Isolated Pulmonary Edema without Myocardial Stunning in Brainstem Strokes - Probasco, John C. (J Neurol Transl Neurosci, 2014)
INTRODUCTION: Ischemic stroke has been associated with stunned myocardium and neurogenic pulmonary edema (NPE). We studied a population of patients with large vessel brainstem ischemic stroke to see if there was an increased risk of pulmonary edema associated with strokes in this region independent of myocardial stunning. HYPOTHESIS: Large vessel ischemic strokes of the brainstem are associated with neurogenic pulmonary edema and occur independently of myocardial stunning. METHODS: This is a retrospective case control study of 1,278 patient admissions. Two hundred ten patients were identified with large vessel ischemic stroke or transient ischemic attack (mean age 65 years, 55% female, 50% black). Infarction locations included: brainstem (N=22), right middle cerebral artery involving the insula (N=38), left middle cerebral artery involving the insula (N=37), and transient ischemic attack (N=113). Multivariate logistic regression models for presence of echocardiographic wall motion abnormalities, QTc-interval prolongation, elevated serum troponin, and pulmonary edema were developed to examine the relative contribution of stroke location and markers of cardiopulmonary dysfunction to each respective outcome, controlling for patient characteristics. RESULTS: Large vessel brainstem stroke was associated with pulmonary edema (adjusted OR 29.23, 95% CI 1.90–449.51) but not cardiac abnormalities. Large vessel left middle cerebral artery stroke was also associated with pulmonary edema (76.44, 6.93–843.54) as well as QTc-interval prolongation (4.55, 10.77–19.24). Large vessel right middle cerebral artery stroke was associated with pulmonary edema (10.88, 1.02–116.70) as well as elevated serum troponin (10.51, 1.71–64.82). CONCLUSION: In a retrospective case control study, large vessel brainstem stroke was associated with the development of pulmonary edema independent of cardiac abnormalities associated with myocardial stunning, suggesting a separate brainstem pathophysiologic mechanism which directly affects the lungs but not the heart.